Genesis and interaction of magmas at Nishinoshima volcano in the Ogasawara arc, western Pacific: new insights from submarine deposits of the 2020 explosive eruptions - Tamura, Yoshihiko; Sato, Tomoki; Ishizuka, Osamu; McIntosh, Iona M.; Yoshida, Kenta; Maeno, Fukashi; Chang, Qing (Frontiers in Earth Science, 2023)
Nishinoshima in the Izu-Ogasawara arc has had historical eruptions in 1973-1974 and from 2013 on and off to the present day. Until mid-June 2020, these eruptions were characterized by effusive Strombolian eruptions of andesite magmas. The andesite magmas of Nishinoshima have been shown to be generated by olivine fractionation of primary andesitic magmas, which are themselves derived from the partial melting of hydrous mantle at relatively low pressures. These andesites comprise the main submarine body of the Nishinoshima edifice, and basalt lavas are observed in the submarine flanks of Nishinoshima and its surrounding knolls. However, in mid-June 2020 Nishinoshima exhibited a sudden transition from effusive Strombolian eruptions of andesite to violent explosive Strombolian eruptions of more mafic magma, leading to tephra fall out over a wide area extending from the island. We present here new geochemical and petrographic data for the submarine deposits of these 2020 eruptions. These demonstrate that as well as the basaltic andesite magma compositions known from subaerial sampling, the full compositional range of the 2020 eruptions spans from basalt to dacite. We present evidence for magma mixing of newly injected basalt with andesite magmas within the crust, which is consistent with eruption observations and previous interpretations. Furthermore, through comparison with previously published data these 2020 eruption deposits yield new insights into magma generation and interaction beneath Nishinoshima. The 2020 Nishinoshima basalts are comparable to the old basalts in the surrounding knolls that were generated through partial melting of mantle at greater depths than that of the primary andesite magmas. Although previously unknown from the main Nishinoshima eruptive center, such basalt magmas could therefore have been generated throughout the entire history of Nishinoshima. We show that the 2020 basaltic andesites resulting from the mixing of new basalt and existing andesite magmas, which resulted in the violent Strombolian eruption, are compositionally similar to a previously reported basaltic andesite sampled from the submarine Nishinoshima edifice. Basaltic andesites were therefore likely also erupted from the main Nishinoshima volcanic center during prehistoric (pre-1973) eruptions, consistent with the idea that basalt magmas could have been generated throughout the entire history of Nishinoshima.